An Analytical Study for Some Drawbacks and Weakness Points of the AES Cipher (Rijndael Algorithm) - Omar A. Dawood; Othman I. Hammadi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The present paper includes a research study about the weak points and the major weakness aspects of the Rijndael cipher from the point of view design. Although several published papers for most researchers around the world included either the developing models or improving techniques by depending on Rijndael cipher. In this study, opposite matter about some scientific criticism for certain essential points in the AES construction will be discussed. When the AES was selected 16 years ago, the digital technologies were quite different from now and the magnitude of the challenges was less, so with the recent advanced technology and the emergence of new applications like Big data’s applications in addition to the applications have run with 64-bit and a lot of other applications, it has become a necessity for designing a new contemporary algorithm for the current demands. Especially young Rijndael that has faded and its sun had set as it has been believed by many researchers. Since the experts and designers of information security in previous time determined its retired date for ten years. In this study, a list of drawbacks and vulnerabilities for the Rijndael internal structure in addition to new recommendations for the future work will be diagnosed. No one denies that the selection of Rijndael was a good choice for civil applications on software and hardware implementations and on many of various platforms, but the excessive speed for the IT progress leads to take in to account recalculation of the security level for the current and perspective future requirements.